Impossible Languages - Moro, Andrea (Book collections on Project MUSE., 2017)
Understanding the nature and the structure of human language coincides with capturing the constraints which make a conceivable language possible or, equivalently, with discovering whether there can be any impossible languages at all. This work explores these related issues, paralleling the effort of a biologist who attempts at describing the class of impossible animals.